2013
DOI: 10.1105/tpc.113.114595
|View full text |Cite
|
Sign up to set email alerts
|

Temporal-Spatial Interaction between Reactive Oxygen Species and Abscisic Acid Regulates Rapid Systemic Acclimation in Plants  

Abstract: Being sessile organisms, plants evolved sophisticated acclimation mechanisms to cope with abiotic challenges in their environment. These are activated at the initial site of exposure to stress, as well as in systemic tissues that have not been subjected to stress (termed systemic acquired acclimation [SAA]). Although SAA is thought to play a key role in plant survival during stress, little is known about the signaling mechanisms underlying it. Here, we report that SAA in plants requires at least two different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
383
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 339 publications
(416 citation statements)
references
References 66 publications
(125 reference statements)
11
383
1
2
Order By: Relevance
“…Each cell along the path of the ROS wave activates its own RBOHD proteins generating a systemic autopropagating wave of ROS production that travels in the apoplast from the initiating tissue to the entire plant at rates of up to 8.4 cm/min (Figure 2). Recent analysis of the ROS wave in Arabidopsis demonstrated that it is required for the activation of SAA of plants in response to local stimuli such as high light or heat, as measured by protein and RNA expression as well as enhanced tolerance of systemic leaves (Suzuki et al, 2013). These finding demonstrated that the ROS wave has a biological function in plants.…”
Section: The Role Of the Ros And Calcium Waves In Saamentioning
confidence: 65%
See 4 more Smart Citations
“…Each cell along the path of the ROS wave activates its own RBOHD proteins generating a systemic autopropagating wave of ROS production that travels in the apoplast from the initiating tissue to the entire plant at rates of up to 8.4 cm/min (Figure 2). Recent analysis of the ROS wave in Arabidopsis demonstrated that it is required for the activation of SAA of plants in response to local stimuli such as high light or heat, as measured by protein and RNA expression as well as enhanced tolerance of systemic leaves (Suzuki et al, 2013). These finding demonstrated that the ROS wave has a biological function in plants.…”
Section: The Role Of the Ros And Calcium Waves In Saamentioning
confidence: 65%
“…This finding prompted the hypothesis that the ROS wave functions to prime the plant for SAA activation and that other stress-specific signals are required to convey specificity to this response. During the SAA response to heat stress, the ROS wave was found to function in coordination with ABA in systemic tissues (Suzuki et al, 2013). This analysis of the ROS wave in Arabidopsis also identified a functional link between ROS production by RBOH proteins and electric signals.…”
Section: The Role Of the Ros And Calcium Waves In Saamentioning
confidence: 85%
See 3 more Smart Citations